2004
DOI: 10.1111/j.1365-2125.2004.02232.x
|View full text |Cite
|
Sign up to set email alerts
|

Drugs with anticholinergic properties and cognitive performance in the elderly: results from the PAQUID Study

Abstract: ObjectivesTo measure the association between the use of drugs with anticholinerg ic properties and cognitive performance in an elderly population, the PAQUID cohort. MethodsThe sample studied was composed of 1780 subjects aged 70 and older, living at home in South western France. Data on socio-demographic characteristics, medical history and drug use were collected using a standardized questionnaire. Cognitive performance was assessed using the following neuropsycholog ical tests: the MiniMental State Examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
132
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(139 citation statements)
references
References 50 publications
3
132
4
Order By: Relevance
“…18 A study of a large population of elderly outpatients found that 13.7% of the subjects were on anticholinergic drugs. 12 A recent study of anticholinergic drug prescriptions indicated that 35.4% of patients receiving an acetylcholinesterase inhibitor also received an anticholinergic drug. 19 Our figure of 24.2% shows a lower result in a rural and remote population with cognitve symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 A study of a large population of elderly outpatients found that 13.7% of the subjects were on anticholinergic drugs. 12 A recent study of anticholinergic drug prescriptions indicated that 35.4% of patients receiving an acetylcholinesterase inhibitor also received an anticholinergic drug. 19 Our figure of 24.2% shows a lower result in a rural and remote population with cognitve symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, drugs with anticholinergic activities are relatively contraindicated in the elderly even in the absence of dementia. [10][11][12] A significant number of drugs without prominent anticholinergic effects have also been shown to contribute to cognitive impairment in elderly patients. 13 Benzodiazepines, in particular, have been implicated as potentially problematic in older adults.…”
mentioning
confidence: 99%
“…Cholinesterase inhibitors have been shown to improve cognitive function (20). Several clinical studies showed that drugs with anti-cholinergic effects had negative effects on the cognitive function of patients (33)(34)(35). Thus, it's possible that cholinergic function impairment may participate in the development of POCD.…”
Section: Mechanismsmentioning
confidence: 99%
“…Cholinergic pathway participates in various cognitive processes including short-term memory, learning and attention (33). The deterioration and impairment of central cholinergic system is not only related to normal aging (33), but also to neurodegenerative diseases such as AD (20). Cholinesterase inhibitors have been shown to improve cognitive function (20).…”
Section: Mechanismsmentioning
confidence: 99%
“…4 There is also a link with poor cognitive outcomes, especially in the group with existing cognitive impairment. 4,5,[26][27][28][29][30][31][32] Anti-cholinergic medications can precipitate delirium and intensify pre-existing delirium. 8,25,[33][34][35][36][37][38][39][40] An episode of delirium is linked to significant morbidity and mortality, and is associated with increased length of hospital stay, institutionalisation, irreversible functional and cognitive decline, and mortality in the elderly.…”
Section: Excluded (N=1487)mentioning
confidence: 99%